Peran Strategis Guru PPKN dalam Meningkatkan Minat Belajar Siswa Inklusi Di SMA Muhammadiyah 1 Cimahi - Sari, Wulan; Martini, Eneng; Hendriawan, Erry (STKIP Pasundan, 2025)
This study aims to optimize the role of Civic Education (PPKn) teachers in enhancing the learning interest of inclusive students, enabling them to develop independent motivation while helping teachers achieve expected learning outcomes. The research addresses several key questions: (1) How is PPKn learning implemented at SMA Muhammadiyah 1 Cimahi? (2) What is the level of learning interest among inclusive students in PPKn subjects? (3) What obstacles do teachers face in fostering learning interest among inclusive students? A qualitative descriptive approach was used, with data collected through interviews, observations, and documentation. The findings reveal insights into how PPKn learning is conducted, the extent of inclusive students' interest in learning, and the challenges teachers encounter. This research contributes to a deeper understanding of the learning dynamics and supports the development of a more inclusive, engaging, and motivating learning environment for all students. Keywords: Teacher optimization, Pancasila and citizenship education